Inhibition of spleen tyrosine kinase (syk) suppresses renal fibrosis through anti-inflammatory effects and down regulation of the MAPK-p38 pathway. (May 2016) - Chen, Kuan-Hsing; Hsu, Hsiang-Hao; Yang, Huang-Yu; Tian, Ya-Chung; Ko, Yi-Ching; Yang, Chih-Wei; Hung, Cheng-Chieh
Graphical abstract: Abstract: Renal fibrosis results from an excessive accumulation of extracellular matrix that occurs in most types of chronic kidney disease. Among the many fibrogenic factors that regulate renal fibrotic processes, transforming growth factor-β1 (TGF-β1) and inflammation after injury play critical roles. Spleen tyrosine kinase (Syk) is important for signaling processes implicated in autoimmune, inflammatory, and allergic diseases. We examined the effects of Syk inhibition on renal fibrosis in vivo and on TGF-β1-induced renal fibroblast activation in vitro . A unilateral ureteral obstruction (UUO) model was induced in male B6 mice. Mice with UUO were administered a Syk inhibitor or saline intraperitoneally 1 day before UUO surgery and daily thereafter. Both kidneys were harvested 7 days after surgery for further analysis. For the in vitro experiments, NRK-49F rat fibroblasts were pre-incubated with a Syk inhibitor before TGF-β1 stimulation. The inhibitory effects of Syk inhibition on signaling pathways down-stream of TGF-β1 were analyzed. In the UUO mouse model, administration of a Syk inhibitor attenuated extracellular matrix protein deposition and expression of α-smooth muscle actin, type I collagen, and fibronectin in a dose-dependent manner. In addition, macrophage infiltration in UUO kidney was reduced by Syk inhibition. Pre-incubation of NRK-49F cells with a Syk inhibitor suppressed TGF-β1-induced myofibroblast activation. Furthermore, inhibitory effects of Syk inhibition on TGF-β1-mediated myofibroblast activation were associated with down-regulation of MAPK-p38. These results suggest that Syk inhibition reduces tubulointerstitial fibrosis in UUO mice and inhibits TGF-β1-induced kidney myofibroblast activation. Syk inhibition could have therapeutic potential for the treatment of renal tubulointerstitial fibrosis.